PROTEKT, Oncofertility Consortium and the Danish Fertility-Preservation Networks - What Can We Learn From Their Experiences? - Michael von Wolff; Claus Yding Andersen; Teresa K Woodruff; Frank Nawroth (SAGE Publishing, 2019)
Fertility preservation is an increasingly important discipline. It requires close coordination between reproductive medicine specialists, reproductive biologists, and oncologists in various disciplines. In addition, it represents a particular health policy challenge, since fertility-protection measures are to be understood as a treatment for side effects of gonadotoxic treatments and would therefore normally have to be reimbursed by health insurance companies. Therefore, it is inevitable that fertility-preservation activities should organise themselves into a network structure both as a medical-logistic network and as a professional medical society. The necessary network structures can differ significantly at regional, national, and international level, as the size of the regions to be integrated and the local cultural and geographical conditions, as well as the political conditions are very different. To address these issues, the current review aims to point out the basic importance and the chances but also the difficulties of fertility-protection networks and give practical guidance for the development of such network structures. We will not only discuss network structures theoretically but also present them based on three established, different sized networks, such as the Danish Network ( www.rigshospitalet.dk ), representing a centralised network in a small country; the German-Austrian-Swiss network Ferti PROTEKT ® ( www.fertiprotekt.com ), representing a centralised as well as decentralised network in a large country; and the Oncofertility ® Consortium ( www.oncofertility.northwestern.edu ), representing a decentralised, internationally oriented network, primarily serving the transfer of knowledge among its members.